2017
DOI: 10.15171/ehem.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of health effects (morbidity and mortality) attributed to PM10 and PM2.5 exposure using an Air Quality model in Bukan city, from 2015-2016 exposure using air quality model

Abstract: Background: Air Quality software is a useful tool for assessing the health risks associated with air pollutants. Quantifying the effects of exposure to air pollutants in terms of public health has become a critical component of policy discussion. The present study purposed to quantify the health effects of particulate matters on mortality and morbidity in a Bukan city hospital from 2015-2016. Methods: Information regarding coordinates, exposed population, number of stations used in profiling, mean and maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…IR ing and IR inh are ingestion and inhalation rate, respectively. IR ing and IR inh are 100 and 20, respectively [3] , [4] , [5] . After calculating of ADD, Hazard quotients, HQ, was determined.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…IR ing and IR inh are ingestion and inhalation rate, respectively. IR ing and IR inh are 100 and 20, respectively [3] , [4] , [5] . After calculating of ADD, Hazard quotients, HQ, was determined.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…In Bukan, cardiovascular mortality accounts for 2% of total deaths. The Air Quality model was used to predict the deaths of 92.2 people dealing with hospitalization due to respiratory disease (25).…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Environmental Protection Agency, the standard concentrations of PM 2.5 and PM 10 are 150 and 65 μg/m 3 , respectively. Unfortunately, the study results showed that the concentration of PM 2.5 and PM 10 in the city is worrying [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%